Analysis of Math Learning Difficulties In Students Mts N 1 Pandeglang In The Covid-19 Pandemic - Setiawan, Irfan Agus; Hendriana, Benny (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This study is a descriptive qualified study conducted on class VII students at MTsN 1 Pandeglang who are conducting online learning with the aim of knowing the factors that cause math learning difficulties in students. Data collection techniques use questionnaire sheets, interviews, and documentation. The sample in this study was 30 students of class VII. Results from research show that students have difficulty learning mathematics. The results of the analysis found five factors that affect student learning difficulties, namely teacher influence 36.67%, family to children's learning 48.89%, student interest when learning mathematics 34.4%, student concentration when learning mathematics 43.4%, students' confidence when studying mathematics 45.56%. So in conclusion, the cause of the problem of learning mathematics based online in class VII in MTsN 1 Pandeglang is external factors and internal factors. External factors include inattention from parents and inappropriate teacher methods when teaching and learning. Internal factors include lack of interest in learning, weak concentration of students, and lack of self-confidence.